PENGARUH KONFLIK PERAN GANDA DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA (Studi Kasus pada Kelompok Perempuan Penjual Rujak di Kabupaten Maluku Tengah) - Septina Louisa Siahaya; Chrestiana - Aponno (Politeknik Negeri Ambon, 2019)
This study aims to determine the effect of multiple conflicts and work environment on the work productivity of rujak woman sellers both partially and simultaneously. The population in this study were all female rujak sellers in Natsepa beach, Sopapei beach and Liang beach. The sample selection was taken by purposive sampling and hypothesis testing was carried out using multiple regression analysis. The results of the study show that simultaneously, there is an influence between multiple role conflict and work environment on work productivity which is indicated by a significance value of 0.000. The same thing is also shown in its partial effect, with a significance value of each under 0.05